2017
DOI: 10.1108/ejm-02-2016-0074
|View full text |Cite
|
Sign up to set email alerts
|

Estimating umbrella-branding spillovers: a retailer perspective

Abstract: Purpose The starting conjecture is that the market share of a brand in one category benefits from its performance in another category, and vice versa. The purpose of this paper is to assess the umbrella-branding spillovers by investigating the presence of synergy effect between categories when a retailer and/or a manufacturer decide to adopt/use the same name for his products. In fact, besides the cross-category dependency due to substitutability or complementarity, products can also be linked through their br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Umbrella or family branding is often motivated on the assumption that the common brand name leads to a “connection in consumers’ minds,” which generalizes consumers’ preferences to the different product categories using the name (Fry 1967, p. 237). The underlying idea for such a halo or spillover effect is that one can not only take advantage of increased brand recognition and recall because of the added exposure potential but also leverage the reputation of the brand across categories (Sebri and Zaccour 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Umbrella or family branding is often motivated on the assumption that the common brand name leads to a “connection in consumers’ minds,” which generalizes consumers’ preferences to the different product categories using the name (Fry 1967, p. 237). The underlying idea for such a halo or spillover effect is that one can not only take advantage of increased brand recognition and recall because of the added exposure potential but also leverage the reputation of the brand across categories (Sebri and Zaccour 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Further, the brand signals that both existing and future products under the same brand will also meet customer expectations, that is, brand‐quality expectations (Aaker & Keller, 1990; Silberhorn et al, 2017). Therefore, when making decisions about a new product, customers use their prior experience with the brand to reduce their perceived risk, especially when quality information is missing or not fully employed (Erdem & Chang, 2012; Sebri & Zaccour, 2017).…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…Prior literature on cross‐buying has documented that customers' brand preferences result in purchases from multiple categories and thus benefit firms by improving the duration of customer relationships (Dahana et al, 2018; Verhoef et al, 2001), purchase frequency (Reinartz et al, 2008; Venkatesan & Kumar, 2004), and profitability (Béal et al, 2019; Shah et al, 2012). In these studies, the mechanism behind the cross‐category spillover is that a need to transfer quality perceptions across categories arises from uncertainty about the true product quality because of asymmetric and imperfect information and thus customers' brand preferences can be correlated across categories (Erdem et al, 2006; Sebri & Zaccour, 2017). In the context of brand extensions, such correlated perceptions across product categories under the same brand are driven by beliefs about the brand, such that the firm's skill level or other key inputs determine the quality of all products it manufactures, and the firm has incentives to use the same brand for products that are similar in quality (i.e., brand trust; Krystallis, 2015; Miklós‐Thal, 2012).…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…Umbrella branding, also known as family branding (Keller et al , 2020), brand leveraging (Lane, 2000), brand stretching (Pepall and Richards, 2002) and brand extension (Völckner and Sattler, 2006), is widely used by modern multiproduct firms (Rasmusen, 2016; Sebri and Zaccour, 2017). The main premise of umbrella branding is that when consumers are uncertain about a certain product’s attributes, they may make inferences about them based on their experience with another product of the same brand (Erdem et al , 2006; Miklós-Thal, 2012).…”
Section: Umbrella Branding and Brand Placement Repetitionmentioning
confidence: 99%
“…Umbrella branding, the use of the same brand name for several products (i.e. complements, substitutes or independent products) developed by the company, is a popular strategy in modern business practice (Keller et al , 2020; Miklós-Thal, 2012; Sebri and Zaccour, 2017). Prior research has demonstrated that umbrella branding can help manufacturers reduce marketing costs and the risk of introducing new products, improve productivity and even alleviate moral hazard (Aaker, 1990; Erdem and Sun, 2002; Hakenes and Peitz, 2008; Rasmusen, 2016).…”
Section: Introductionmentioning
confidence: 99%